(untitled) (Dhaka University Journal of Biological Sciences, 2022)
Bangladesh is an over populated country with a high incidence of traumaticbrain injury (TBI) for which neuropsychological services are only just emerging.In this context the present study undertook in a culturally sensitive manner totranslate into Bangla (Bengali) the Brain Injury Questionnaire of Sexuality (BIQS)and to present findings from a sample of TBI patients. Standard proceduresincluding back translation for scale adaptation were followed. The Banglaversion of BIQS (BIQS-B) were applied on 30 TBI and 53 healthy sample. Factorand principle component analysis of the BIQS-B yielded three components as inthe original scale explaining 75.3% of the total variance. Reliability is satisfactory,matching that of the English version. The TBI sample scored lower on the BIQS-Bthan did the healthy controls by virtue of not reporting the positive changes insexuality over time that the health controls reported (means of 43.90 vs 52.02, p <0.001). In a very different culture, the factor structure of the BIQS-B is in factsimilar to the English version and has acceptable reliability and validity, hencecontributing to the goal of improving access to services not just in Bangladeshbut in Bangla speaking minority ethnic groups in other countries. Dhaka Univ. J. Biol. Sci. 31(1): 183-191, 2022 (January)